Melioidosis vaccines: a systematic review and appraisal of the potential to exploit biodefense vaccines for public health purposes - Peacock, S; Limmathurotsakul, D; Lubell, Y; Koh, G; White, L; Day, N; Titball, R (Public Library of Science, 2012)
Background: Burkholderia pseudomallei is a Category B select agent and the cause of melioidosis. Research funding for vaccine development has largely considered protection within the biothreat context, but the resulting vaccines could be applicable to populations who are at risk of naturally acquired melioidosis. Here, we discuss target populations for vaccination, consider the cost-benefit of different vaccination strategies and review potential vaccine candidates. Methods and Findings: Melioidosis is highly endemic in Thailand and northern Australia, where a biodefense vaccine might be adopted for public health purposes. A cost-effectiveness analysis model was developed, which showed that a vaccine could be a cost-effective intervention in Thailand, particularly if used in high-risk populations such as diabetics. Cost-effectiveness was observed in a model in which only partial immunity was assumed. The review systematically summarized all melioidosis vaccine candidates and studies in animal models that had evaluated their protectiveness. Possible candidates included live attenuated, whole cell killed, sub-unit, plasmid DNA and dendritic cell vaccines. Live attenuated vaccines were not considered favorably because of possible reversion to virulence and hypothetical risk of latent infection, while the other candidates need further development and evaluation. Melioidosis is acquired by skin inoculation, inhalation and ingestion, but routes of animal inoculation in most published studies to date do not reflect all of this. We found a lack of studies using diabetic models, which will be central to any evaluation of a melioidosis vaccine for natural infection since diabetes is the most important risk factor. Conclusion: Vaccines could represent one strand of a public health initiative to reduce the global incidence of melioidosis.